PS5:97 Role of cd107a+ (lamp-1) cytotoxic cd8+ t-cells in patients with sle. (21st March 2018) - Wiechmann, A; Wilde, B; Kribben, A; Witzke, O; Dolff, S
Abstract : Objectives: Cytotoxic T-cells are a thought to play a pivotal role in the pathogenesis of systemic lupus erythematosus (SLE) in particular in lupus nephritis. The aim of this study was to investigate the activation marker CD314 (NKG2D) and CD107a (LAMP-1) on cytotoxic CD8 +T cells in patients with systemic lupus erythematosus. Methods: Peripheral blood of patients with systemic lupus erythematosus (n=30) and healthy controls (n=21) was stained with anti-CD8 (PB), -CD3 (Chrom Orange), -CD45RO (FITC), -CD197 (PE), -CD314 (APC), -CD107a (APC) antibodies and analysed by flow cytometry. Kidney biopsies of lupus nephritis patients were investigated by immunohistochemistry and immunofluorescence for the presence of CD8 +C107a+cells. Patients disease activity was assessed by systemic lupus erythematosus disease activity index (SLEDAI). Results: The percentages of CD314 +on CD8+T cells were not different between SLE-patients and healthy controls. The percentages of CD107a+on CD8+T cells were significantly decreased in SLE-patients as compared to healthy controls (40.2%±18.5% vs 47.9±15.0%, p=0.02). This was even more significant in SLE-patients with inactive disease. The evaluation of lupus nephritis biopsies showed a significant number of CD107a+CD8+T cells mainly located in the peritubular infiltrates. Conclusions: These results demonstrate that CD8 +T cells of patients with systemic lupus erythematosus have an altered activation status which seems to be associated with disease activity. The proof of intrarenal CD107a+CD8+suggests a role in the pathogenesis of lupus nephritis.